Relationship between edema and intracranial pressure following intracerebral hemorrhage in rat - Kalisvaart, Anna C. J.; Bahr, Natasha A.; Colbourne, Frederick (Frontiers in Stroke, 2023)
Elevated intracranial pressure (ICP) is a potentially fatal consequence of intracerebral hemorrhage (ICH). As the mass of the hematoma and regional edema builds, ICP rises and becomes increasingly variable acutely after stroke. High ICP may worsen cellular injury and edema by impairing local tissue perfusion, fueling a cycle that may ultimately cause fatality through ischemia and brain herniation. Time spent above an ICP of 20 mmHg often predicts a greater risk of death and disability following ICH. Compensatory mechanisms combat rising ICP. Classically, these include cerebrospinal fluid volume loss and cerebrovascular autoregulation, such as a reduction in the volume of venous blood. Additional mechanisms such as brain tissue compliance and skull volume compensation may also contribute. Compensatory compliance mechanisms are limited, and they vary by age and many other factors. Animal models of ICH are widely used to assess these variables and to gauge putative therapeutics. Most often those studies rely upon simple measures of edema, which may not accurately predict ICP data. Thus, we analyzed our past studies characterizing ICP, edema, and tissue compliance responses to striatal ICH in rat, including the collagenase (C-ICH) and whole blood models (WB-ICH). We found that both ICH models raised ICP, with greater effects in the C-ICH model, which may thus better reflect clinical findings of concern. Importantly, measures of edema, such as in the damaged hemisphere, on their own are not predictive of average or peak ICP response within either model, unless assessing across a very wide range of injury severities, or when including non-stroke animals. We caution against using edema data as a surrogate measure of mass effect and ICP following ICH.